Evaluasi dan Peningkatan Performansi Lini Perakitan Kendaraan Khusus Menggunakan Metode Line Balancing pada PT. Pindad (Persero) - Mohammad Fikar Usman Mustofa; Fais Hamzah; Renanda Nia Rachmadita (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Assembly lines that have poor efficiency result in various problems in the production process, one of which is the bottleneck problem. PT. Pindad (Persero) as a manufacturing company, has problems in the assembly line for special vehicles, where the efficiency of the assembly line has an unclear and uneven distribution of workloads, this results in poor production efficiency. This study aims to valuate the efficiency of PT. Pindad (Persero) and produce alternative improvements. An evaluation of the Komodo tactical vehicle product assembly line was conducted using line efficiency, balance delay, and smoothest index. It is known that the existing assembly line has a line efficiency of 13.25%, a balance delay of 86.75%, and a smoothest index of 875.31. Then the line balance is improved using heuristic line balancing methods. The methods used include the largest candidate rule, ranked positional weight, and regional approach. The results of this study are recommendations for special vehicle assembly lines using the line balancing ranked positional weight method with a line efficiency value of 94.1%, balance delay of 5.9%, and smoothest index of 8.86.